Effects of temperature and strain rate on commercial aluminum alloy AA5083 - Mohd Nor, Mohd Khir (Trans Tech Publications Inc, 2014)
Superplastic forming, SPF is a special metalworking process that allows sheets of metal alloys such as aluminum to be stretched to lengths over ten times. Nowdays, only a few aluminium alloys can meet the specific requirement of SPF manufacturing process and not much data available to represent their mechanical behaviour. In order to deal with this issue, this research project is conducted to investigate the characteristics of commercial aluminum alloy, AA5083 when tested at different strain rates and temperatures. These parameters play a crucial roles in the design and manufacturing processes of military, automotive and aerospace structures. Equally, the effects must be considered in the constitutive model development to accurately capture the deformation behaviour of such materials. The specimens were prepared according to 12.5mm gauge length standard. The Uniaxial Tensile Tests were carried out at various strain rate from 4.167 x10-1 s-1 to 4.167 x10-5 s-1 over a wide temperature range from ambient to 95°C. The experimental data shows that increasing strain rate increases flow stress, while increasing temperature decrease flow stress. This is leads to important conclusion that material AA5083 exhibits strain rate and temperature sensitivite, and suit with the SPF operating condition.